Mitochondria as an important target of metformin: The mechanism of action, toxic and side effects, and new therapeutic applications - Jin Feng; Xiaohui Wang; Xiaochun Ye; Irma Ares; Bernardo Lopez-Torres; Marta Martínez; María-Rosa Ma; Xu Wang; Arturo Anadón; María-Aránzazu Martínez (Elsevier, 2022)
Metformin is the oldest and most commonly used first-line antidiabetic drug because of its good clinical efficacy, high safety, low cost and easy access. At the same time, in recent years, we have found that its role as a therapeutic drug is gradually expanding. A large number of basic studies have shown that metformin may become a promising attractive candidate for drug repurposing. Therefore, it is extremely beneficial to conduct an in-depth discussion on the main mechanism of metformin. As early as the year 1950, studies showed that metformin played a biological role by regulating mitochondria. Then, ground-breaking studies showed that metformin functions by inhibiting complex I in the mitochondrial respiratory chain. Although there are still many controversies about the key molecular targets of metformin, with the emergence of more and more evidence, it gradually came to be concluded that mitochondria play a central role in the application of metformin. Mitochondria are important fulcrums for cell functions. The exact mechanism of action in mitochondria of this pleiotropic anti-hyperglycaemic molecule is still unclear. This review article explores the core role of mitochondria in the pharmacological and toxicological effects of metformin, and summarises the mechanism of action if metformin in mitochondria. It also provides ideas and supporting evidence for the re-development and reuse of metformin as an old drug, as well as new insight into the treatment of human diseases.